HUBUNGAN TINGKAT PENGETAHUAN DAN PERILAKU PERSONAL HYGIENE TERHADAP KEJADIAN PEDIKULOSIS PADA ANAK SD DI NUSA PENIDA - Bisma Krisnanda, I Kadek; Sri Laksemi, Dewa Ayu Agus; Asri Damayanti, Putu Ayu; Eka Diarthini, Ni Luh Putu (E-Jurnal Medika Udayana; Vol 13 No 8 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i08.P08, 2024)
ABSTRACT   Pediculosis capitis is an infection that occurs on the human scalp due to an infestation of Pediculus humanus capitis. Pediculosis is characterized by itching on the scalp, in school-age children the infestation of Pediculus humanus capitis has a negative impact on children's learning activities and has the potential to interfere with learning achievement. This study aims to determine whether personal hygiene and knowledge have a relationship with the incidence of pediculosis in elementary school children in Nusa Penida. This study uses an analytic observational study with a Cross Sectional study with univariate analysis techniques and bivariate analysis using the Chi-square test, this study used a sample of 100 samples taken from SD Negeri 2 Ped and SD Negeri 4 Ped, data collection was carried out by using a questionnaire regarding personal hygiene behavior and knowledge of pediculosis and the incidence of pediculosis in research respondents. In this study it was found that out of 100 respondents, 44% had poor personal hygiene, 41% had poor knowledge and 65% experienced pediculosis which is a high number because it exceeds 50% , from this study it was found that personal hygiene had a significant relationship with the incidence of pediculosis (p-value 0.002 and RP = 1.580), and knowledge about pediculosis has a relationship with the incidence of pediculosis (p-value 0.002 and RP = 1.578). So it can be seen that personal hygiene and knowledge about pediculosis is one of the risk factors for the incidence of pediculosis in elementary school children in Nusa Penida. Keywords : Personal hygiene, Knowledge, Pediculosis